2019
DOI: 10.3390/genes10060446
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of Cold Responsive LlaCIPK Gene Enhances Cold Stress Tolerance in Nicotiana tabacum

Abstract: Low-temperature stress severely affects the growth, development, and geographical distribution of various crop plants, resulting in significant economic loss to producers. In a quest to identify cold-regulated genes, we constructed a cDNA suppression subtractive library from a high altitude adapted ecotype of Lepidium. We cloned a cold-induced gene LlaCIPK from the subtracted cDNA library which gave homology to Arabidopsis CIPK15 gene. The predicted 3D structure of LlaCIPK protein also showed homology with Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…CBLs and CIPKs in Arabidopsis revealed that these genes responded to various stresses, including drought, salinity and osmotic stresses 9,14,15 . Similar phenomena were also recently observed on diverse species, such as rice 14,16,17 , maize 18 , wheat 19 , soybean 20 , tobacco 21 , apple 22 , pepper 23 , eggplant 24 , pear 25 and grapewine 26 . However, whether CBL and CIPKs are involved in mediating different stress responses remains largely unknown in alfalfa.…”
Section: Introductionsupporting
confidence: 85%
“…CBLs and CIPKs in Arabidopsis revealed that these genes responded to various stresses, including drought, salinity and osmotic stresses 9,14,15 . Similar phenomena were also recently observed on diverse species, such as rice 14,16,17 , maize 18 , wheat 19 , soybean 20 , tobacco 21 , apple 22 , pepper 23 , eggplant 24 , pear 25 and grapewine 26 . However, whether CBL and CIPKs are involved in mediating different stress responses remains largely unknown in alfalfa.…”
Section: Introductionsupporting
confidence: 85%
“…Meanwhile, there are seven DEGs actively modulated in all abiotic stress exposures, namely, GLR2.5, CNGC12, OSCA1.3, OSCA2.1, CML38, CIPK15, and CIPK16. Previous studies have demonstrated that the expression of GLR2.5 displays a notabe elevation under salt treatment conditions [165] and that the CIPK15 homologous gene could improve cold stress resistance in Nicotiana tabacum [166]. Screening by forward genetics, AtCIPK16 was identified as a mediator diminishing shoot salt accumulation and enhancing salinity tolerance in Arabidopsis and transgenic barley [167].…”
Section: Transcriptomic Analysis Reveals Ca 2+ Regulation Under Abiotic Stressesmentioning
confidence: 99%
“…Analysis of cis-elements in genes could provide critical evidence for the gene's function. Many studies reported that CIPK genes play key roles in various stresses [17,22,25]. Here, the putative stress-related and hormone-related cis-elements were scanned in the 1.5 kb upstream of the start codons of 80 GhCIPKs using the PlantCARE database.…”
Section: Analysis Of Cis-elements and Prediction Of Transcription Facmentioning
confidence: 99%
“…Previous studies reported that CIPK genes could play important roles in plant responses to various stresses [14,22,25,44]. Therefore, we analyzed the expression patterns of the 80 GhCIPKs under various stresses, including cold, hot, salt, and drought stresses, using the published RNA-seq data of TM-1.…”
Section: Expression Profiling Of Ghcipk Genes In Different Tissues Anmentioning
confidence: 99%
See 1 more Smart Citation